(untitled) (Revista de Artes Marciales Asiáticas, 2022)
In judo tournaments, matches for each weight category are held on the same day and athletes competing at the finals have to compete at different times of the day. This study aimed to investigate the effect of time-of-day on judo specific performance and the changes in physiological load following judo specific performance. Fourteen male judo athletes (age 19.1±1.4 years) voluntarily participated in the study. At the 1st visit, anthropometrical measurements and familiarization procedures were conducted and the athletes’ chronotype was determined. Athletes performed the Special Judo Fitness Test (SJFT) during 2nd and 3rd visits. Athletes randomly performed two consecutive SJFTs with 15 min intervals at 10:00h, which is the official start time of matches, and at 18:00h which is the time when the finals start. During SJFT applications, athletes heart rate (HR), blood lactate (bLA), body temperature and rate of perceived exertion (RPE) were monitored. The changes in total throw numbers (F1, 13= 1.32, p=0.27) and SJFT index (F1, 13= 0.30, p=0.59) were not different between morning and evening. There were similar changes in bLA (F4, 52=0.66, p=0.63), RPE (F1, 13=1.42, p=0.26) and body temperature (F1.4, 18.0=1.18, p=0.31) which were measured before and after the tests. However, HR measured in the evening were higher compared to morning measurement at all measurement times (F1, 13=10.28, p=0.01), but there was no difference in SJFT throws (F3.8, 48.8=0.49, p=0.74). In conclusion, different times of the day did not affect judo specific performance as well as physiological variables in judo athletes.